2022
DOI: 10.15252/msb.202110712
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genomic variation on protein phosphorylation states and regulatory networks

Abstract: Genomic variation impacts on cellular networks by affecting the abundance (e.g., protein levels) and the functional states (e.g., protein phosphorylation) of their components. Previous work has focused on the former, while in this context, the functional states of proteins have largely remained neglected. Here, we generated high‐quality transcriptome, proteome, and phosphoproteome data for a panel of 112 genomically well‐defined yeast strains. Genetic effects on transcripts were generally transmitted to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 76 publications
(138 reference statements)
3
37
0
Order By: Relevance
“…The top row shows correlation of the protein’s abundance with heat-induced lag. Fields in all other rows show allelic effects (difference in mean protein abundance between strains carrying the RM allele compared to the BY allele at the indicated loci) and asterisks indicate significant pQTL-target relations as described in (Grossbach et al ., 2022). Columns or proteins were ordered according to hierarchical clustering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The top row shows correlation of the protein’s abundance with heat-induced lag. Fields in all other rows show allelic effects (difference in mean protein abundance between strains carrying the RM allele compared to the BY allele at the indicated loci) and asterisks indicate significant pQTL-target relations as described in (Grossbach et al ., 2022). Columns or proteins were ordered according to hierarchical clustering.…”
Section: Resultsmentioning
confidence: 99%
“…The largest differences were observed at markers coinciding or in linkage disequilibrium with hotspots of protein abundance regulation. Indeed, 7 of 12 pQTL hotspots (as detected in (Grossbach et al, 2022)) showed significant PT score differences at 5 % FDR and proteome-wide effects of pQTL hotspots were often correlated with the effects of chemical inhibition of PKA and TOR (Fig. S3A).…”
Section: Genetic Mapping Of the Pt Network State In The Byxrm Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…The control of protein homeostasis and post-translational modifications (PTM) are also essential components for stress survival across different species (Zhang et al, 2015;Kosová et al, 2021). Strikingly, there is growing evidence that state changes of key regulatory proteins are associated with more dramatic functional alterations for the cell than protein abundance (Needham et al, 2019;Ochoa et al, 2019;Mehnert et al, 2020;Grossbach et al, 2022). Actually, several specific phosphorylation states have been correlated to a number of stress resistance traits in the context of a novel high-quality multi-omics QTL study in yeast, showing, for the first time at a global scale, the central importance of protein phosphorylation to adapt stress responses in living organisms (Grossbach et al, 2022).…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%
“…Strikingly, there is growing evidence that state changes of key regulatory proteins are associated with more dramatic functional alterations for the cell than protein abundance (Needham et al, 2019;Ochoa et al, 2019;Mehnert et al, 2020;Grossbach et al, 2022). Actually, several specific phosphorylation states have been correlated to a number of stress resistance traits in the context of a novel high-quality multi-omics QTL study in yeast, showing, for the first time at a global scale, the central importance of protein phosphorylation to adapt stress responses in living organisms (Grossbach et al, 2022). However, the study of protein state changes in response to arsenic, including PTMs, is poorly developed, although there are some examples pointing to their relevance in arsenic signaling.…”
Section: Post-transcriptional Regulationmentioning
confidence: 99%